2008
DOI: 10.1021/ac800464g
|View full text |Cite
|
Sign up to set email alerts
|

Natural Organic Matter and the Event Horizon of Mass Spectrometry

Abstract: Soils, sediments, freshwaters, and marine waters contain natural organic matter (NOM), an exceedingly complex mixture of organic compounds that collectively exhibit a nearly continuous range of properties (size-reactivity continuum). NOM is composed mainly of carbon, hydrogen, and oxygen, with minor contributions from heteroatoms such as nitrogen, sulfur, and phosphorus. Suwannee River fulvic acid (SuwFA) is a fraction of NOM that is relatively depleted in heteroatoms. Ultrahigh resolution Fourier transform io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
454
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(489 citation statements)
references
References 73 publications
31
454
1
3
Order By: Relevance
“…This result suggests that constituents of NOM with lower O/C ratio are preferentially ionized in MALDI negative mode, whereas in ESI negative mode, constituents of NOM with higher O/ C ratio (as compared with MALDI uniquely identified compounds) are preferentially ionized. The selectivity of ESI in negative mode for NOM observed in our work coincides with a previous study reported by Hertkorn et al [8].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This result suggests that constituents of NOM with lower O/C ratio are preferentially ionized in MALDI negative mode, whereas in ESI negative mode, constituents of NOM with higher O/ C ratio (as compared with MALDI uniquely identified compounds) are preferentially ionized. The selectivity of ESI in negative mode for NOM observed in our work coincides with a previous study reported by Hertkorn et al [8].…”
Section: Resultssupporting
confidence: 93%
“…As a result, the extent of molecular information about NOM is largely restricted. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), due to its ultrahigh resolution and mass accuracy, can provide molecular elemental information about NOM without chromatographic separation [5,6], and has been used for accurate characterization of NOM [7][8][9]. Electrospray ionization (ESI) is the most commonly used ionization method for FT-ICR-MS characterization of NOM because it is one of the softest ionization methods and can be easily coupled with FT-ICR-MS [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small discrepancies observed likely resulted from ionization selectivity, 45 which probably favored detection of aliphatic carboxylic acids with low O/C ratios, thereby explaining the small gain in H/C ratios and tiny decrease in O/C ratios.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Recently, ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has been successfully used to characterize the previously unknown Cl-DBPs and Br-DBPs (Zhang et al, 2012a;Zhang et al, 2012b;Lavonen et al, 2013;Zhang et al, 2014). The ultrahigh resolution and mass accuracy of FT-ICR MS combined with electrospray ionization (ESI) allows the determination of unambiguous and exact molecular formulas (Stenson et al, 2003;Kim et al, 2006aKim et al, , 2006bHertkorn et al, 2008). It is thus anticipated that the ESI FT-ICR MS method could also be suitable for identifying the molecular formulas of unknown I-DBPs.…”
Section: Introductionmentioning
confidence: 99%